A ketocarotenoid‐based colour polymorphism in the Sira poison frog Ranitomeya sirensis indicates novel gene interactions underlying aposematic signal variation. Issue 11 (9th June 2020) - Twomey, Evan; Johnson, James D.; Castroviejo‐Fisher, Santiago; Van Bocxlaer, Ines
Abstract: The accumulation of red ketocarotenoids is an important component of coloration in many organisms, but the underlying mechanisms are poorly understood. In some organisms, ketocarotenoids are sequestered from the diet and can accumulate when enzymes responsible for carotenoid breakdown are disrupted. In other organisms, ketocarotenoids are formed endogenously from dietary precursors via oxidation reactions carried out by carotenoid ketolase enzymes. Here, we study the genetic basis of carotenoid coloration in an amphibian. We demonstrate that a red/yellow polymorphism in the dendrobatid poison frog Ranitomeya sirensis is due to the presence/absence of ketocarotenoids. Using whole‐transcriptome sequencing of skins and livers, we found that a transcript encoding a cytochrome P450 enzyme (CYP3A80) is expressed 3.4‐fold higher in livers of red frogs versus yellow. As CYP3A enzymes are known carotenoid ketolases in other organisms, our results point to CYP3A80 as a strong candidate for a carotenoid ketolase in amphibians. Furthermore, in red frogs, the transcript encoding the carotenoid cleavage enzyme BCO2 is expressed at a low level or as a splice variant lacking key catalytic amino acids. This suggests that BCO2 function may be disrupted in red frogs, providing a mechanism whereby the accumulation of ketocarotenoids and their dietary precursors may be enhanced.